A new research proposal to prevent hydrogen embrittlement for nuclear waste container by bacteria-a mini review - Zhang, Qichao; Jiang, Yishan; Zhao, Xin; Duan, Jizhou; Chen, Luning; Xu, Ying (Frontiers in Microbiology, 2023)
A large amount of nuclear waste produced in the process of nuclear energy utilization has always been a key problem to be solved urgently for nuclear safety. At present, “deep geological disposal” is a feasible method and generally accepted by many countries. The oxygen content in the near field environment of the waste container will decrease to anaerobic conditions, and hydrogen will permeation into the internal materials of container for a long time. Hydrogen evolution corrosion may cause a risk of hydrogen embrittlement. The harm of hydrogen embrittlement in metal container is far more severe than predictable uniform corrosion. It is a research hotspot that the microorganisms impact on the corrosion behavior of container materials in the deep geological environment. Microbial corrosion in deep geological environments can be divided into two types: aerobic microbial corrosion and anaerobic microbial corrosion. There is a type of hydrogen consuming microorganism in the natural environment that uses the oxidation of hydrogen as the energy for its life activities. This provides a new approach for us to study reducing the hydrogen embrittlement sensitivity of nuclear waste container materials.